Extracellular vesicles from Heligmosomoides bakeri and Trichuris muris contain distinct microRNA families and small RNAs that could underpin different functions in the host. Issue 9 (August 2020) - White, Ruby; Kumar, Sujai; Chow, Franklin Wang-Ngai; Robertson, Elaine; Hayes, Kelly S.; Grencis, Richard K.; Duque-Correa, María A.; Buck, Amy H.
Graphical abstract: Highlights: Many small RNAs in extracellular vesicles (EVs) from diverse nematodes derive from intergenic and repetitive elements. The parasite microRNA (miRNA) content of EVs is consistent across multiple EV isolation protocols and laboratories. Trichuris muris and Heligmosomoides bakeri EVs contain distinct parasite miRNA family members. Trichuris muris EVs purified across different laboratories consistently contain more mouse miRNAs than H. bakeri . Comparisons of helminth EV cargos could help identify sRNAs involved in cross-species communication and niche specificity. Abstract: Extracellular vesicles (EVs) have emerged as a ubiquitous component of helminth excretory-secretory products that can deliver parasite molecules to host cells to elicit immunomodulatory effects. RNAs are one type of cargo molecule that can underpin EV functions, hence there is extensive interest in characterising the RNAs that are present in EVs from different helminth species. Here we outline methods for identifying all of the small RNAs (sRNA) in helminth EVs and address how different methodologies may influence the sRNAs detected. We show that different EV purification methods introduce relatively little variation in the sRNAs that are detected, and that different RNA library preparation methods yielded larger differences. We compared the EV sRNAs in the gastrointestinal nematode Heligmosomoides bakeri with those in EVs from the distantly related gastrointestinal nematode Trichuris muris, and found that many of the sRNAs in both organisms derive from repetitive elements or intergenic regions. However, only in H. bakeri do these RNAs contain a 5′ triphosphate, and Guanine (G) starting nucleotide, consistent with their biogenesis by RNA-dependent RNA polymerases (RdRPs). Distinct microRNA (miRNA) families are carried in EVs from each parasite, with H. bakeri EVs specific for miR-71, miR-49, miR-63, miR-259 and miR-240 gene families, and T. muris EVs specific for miR-1, miR-1822 and miR-252, and enriched for miR-59, miR-72 and miR-44 families, with the miR-9, miR-10, miR-80 and let-7 families abundant in both. We found a larger proportion of miRNA reads derive from the mouse host in T. muris EVs, compared with H. bakeri EVs. Our report underscores potential biases in the sRNAs sequenced based on library preparation methods, suggests specific nematode lineages have evolved distinct sRNA synthesis/export pathways, and highlights specific differences in EV miRNAs from H. bakeri and T. muris that may underpin functional adaptation to their host niches.